x=4(x-1)+1

Simple and best practice solution for x=4(x-1)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=4(x-1)+1 equation:


Simplifying
x = 4(x + -1) + 1

Reorder the terms:
x = 4(-1 + x) + 1
x = (-1 * 4 + x * 4) + 1
x = (-4 + 4x) + 1

Reorder the terms:
x = -4 + 1 + 4x

Combine like terms: -4 + 1 = -3
x = -3 + 4x

Solving
x = -3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
x + -4x = -3 + 4x + -4x

Combine like terms: x + -4x = -3x
-3x = -3 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3x = -3 + 0
-3x = -3

Divide each side by '-3'.
x = 1

Simplifying
x = 1

See similar equations:

| y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 |

Equations solver categories